Motion Control for Autonomous Navigation in Blue and Narrow Waters Using Switched Controllers - Angelo Alessandri (Journal of Marine Science and Engineering, 2019)
Autonomous ships represent one of the new frontiers of technological innovation in marine engineering, which demand the development of innovative control systems to guarantee efficient and safe navigation of vessels. A convenient control system should be able to command the several actuators installed on board in different conditions—for instance, during oceanic navigation, harbor approach, narrow channels, and crowed areas. Such tasks are accomplished by different switching controllers for high and low speed motion, which have to be orchestrated to ensure an effective maneuvering. An approach to the design of hierarchies of controllers for maneuvering and navigation of ships equipped with a standard propulsion configuration in both blue and narrow water is proposed. Different levels of control, from global to local, are defined and integrated to steer the vessel in such a way to increase the maneuvering capability in various scenarios.